Karakteristik Perakaran Tanaman Padi Sawah IR 64 (Oryza sativa, L) pada Umur Bibit dan Jarak Tanam yang Berbeda - Budiastuti Kurniasih, Siti Fatimah, Dwi Ari Purnawati (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2008)
The research aimed to observe rooting characteristic of IR 64 wetland rice grown in different seedling age and crop spacing, in relation to the growth and yield of rice. The experiment was conducted on farmer’s field at Gadingan, Ngluwar, Magelang district from December 2007 to March 2008. The experiment was arranged using 3 x 3 factorial Randomized Completely Block Design (RCBD) with three replications. The first factor was seedling ages which consisted of 3 levels, namely 7 days (U1), 14 days (U2) and 21 days (U3). The second factor was three levels crop spacings, i.e: 10 cm x 10 cm (J1), 20 cm x 20 cm (J2) and 30 cm x 30 cm.The results showed that the difference of seedling age and crop spacing formed different rooting characteristics. The wider crop spacing, the more intensive rooting feature would be. Root volume, total root length and root dry weight of (30x30)cm2 were higher than (10x10)cm2 and (20x20)cm2 crop spacing. There were significant positive correlations between root variables and rice yield per hill. Although the younger seedling reduced date of flowering as well as harvesting age, both seedling age and crop spacing did not affect total rice yield.